2007
DOI: 10.1086/522630
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Antimicrobial Peptides in the Normal and Involved Skin of Patients with Infective Cellulitis

Abstract: In response to cutaneous infection there is a local and distal increase in endogenous antimicrobial peptide mRNA in both involved and normal-appearing skin. These observations show, for the first time to our knowledge, that after infection the human body responds by increasing systemic innate immunity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
9
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 15 publications
(26 reference statements)
4
9
0
Order By: Relevance
“…These findings confirm results from various in vitro studies of cultured keratinocytes exposed to live and heat-inactivated S. aureus (5,13) or to cell wall components of Gram-positive bacteria (12,23) but are contradictory to results from one in vitro study that found GAS to be a poor inducer of HBD-2 (5). Our study adds to the evidence from other in vivo studies demonstrating a strong induction of HBD-2 by Gram-positive bacterial infection (16,24). Our findings, in part presented earlier for a subgroup of patients with S. aureus skin infection (26), are the first, to our knowledge, to demonstrate induction of HBD-3 in response to Gram-positive skin infection in vivo.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…These findings confirm results from various in vitro studies of cultured keratinocytes exposed to live and heat-inactivated S. aureus (5,13) or to cell wall components of Gram-positive bacteria (12,23) but are contradictory to results from one in vitro study that found GAS to be a poor inducer of HBD-2 (5). Our study adds to the evidence from other in vivo studies demonstrating a strong induction of HBD-2 by Gram-positive bacterial infection (16,24). Our findings, in part presented earlier for a subgroup of patients with S. aureus skin infection (26), are the first, to our knowledge, to demonstrate induction of HBD-3 in response to Gram-positive skin infection in vivo.…”
Section: Discussionsupporting
confidence: 82%
“…In fact, it has been shown for HBD-2 that a lesion can cause upregulation even in nonaffected skin via systemic release of inflammatory mediators (24). In our study, such an effect may be present to some degree for HBD-2, as expression in healthy skin was highest in patients with more than 6 recurrences.…”
Section: Discussionsupporting
confidence: 46%
“…A strong relationship has been demonstrated in human patients affected by different inflammatory diseases, such as psoriasis and atopic dermatitis, 28,29 and a marked difference in BD expression in these two diseases (lower in atopy and higher in psoriasis) is probably due to the different immunological patterns that characterize these two inflammatory diseases 30–32 . Recent studies have suggested that the differential expression of AMPs can underlie higher susceptibility to bacterial infection in atopic individuals compared with patients with psoriasis 3,6,23,29–33 …”
Section: Discussionmentioning
confidence: 99%
“…The most popular and main-stream areas of research are new antimicrobial therapeutics [29]. However, alternative therapeutic options are also under investigation, to name: antimicrobial natural compounds [30,31], cationic antimicrobial peptides [32], the use of protection strategy to biofilm formation [33,34] or bacteriophage-based approaches [35,36]. Among the listed, photodynamic inactivation (PDI) of S. aureus is also a promising option.…”
Section: Discussionmentioning
confidence: 99%